Processed xenogenic cartilage as innovative biomatrix for cartilage tissue engineering: Effects on chondrocyte differentiation and function - Schwarz, Silke; Elsaesser, Alexander F.; Körber, Ludwig; Goldberg-Bockhorn, Eva; Seitz, Andreas M.; Bermueller, Christian; Duerselen, Lutz; Ignatius, Anita; Breiter, Roman; Rotter, Nicole (Journal of Tissue Engineering and Regenerative Medicine, 2015)
One key point in the development of new bioimplant matrices for the reconstruction and replacement of cartilage defects is to provide an adequate microenvironment to ensure chondrocyte migration and de novo synthesis of cartilage-specific extracellular matrix (ECM). A recently developed decellularization and sterilization process maintains the three-dimensional (3D) collagen structure of native septal cartilage while increasing matrix porosity, which is considered to be crucial for cartilage tissue engineering. Human primary nasal septal chondrocytes were amplified in monolayer culture and 3D-cultured on processed porcine nasal septal cartilage scaffolds. The influence of chondrogenic growth factors on neosynthesis of ECM proteins was examined at the protein and gene expression levels. Seeding experiments demonstrated that processed xenogenic cartilage matrices provide excellent environmental properties for human nasal septal chondrocytes with respect to cell adhesion, migration into the matrix and neosynthesis of cartilage-specific ECM proteins, such as collagen type II and aggrecan. Matrix biomechanical stability indicated that the constructs retrieve full stability and function during 3D culture for up to 42 days, proportional to collagen type II and GAG production. Thus, processed xenogenic cartilage offers a suitable environment for human nasal chondrocytes and has promising potential for cartilage tissue engineering in the head and neck region. Copyright (C) 2012 John Wiley & Sons, Ltd.
Keywords: cell differentiation; extracellular matrix; cartilage tissue engineering; 3D cell culture; cartilage reconstruction; xenogenic implant matrix